Statistical Study of Financial Soundness Enterprises of JSC "NIZHFARM" ("Journal "U". Economy. Management. Finance.", 2021)
The article provides a statistical study of the financial stability of the NIZHFARM JSC enterprise using econometric methods. In the course of the correlation-regression analysis, it was revealed which factor has the greatest influence on the change in the autonomy coefficient of a given enterprise, and conclusions are drawn.
Keywords: financial stability; KRA; equity ratio; return on assets